Deep-water Holothuroidea (Echinodermata) collected during the TALUD cruises off the Pacific coast of Mexico, with the description of two new species - Claude Massin; Michel E. Hendrickx (Revista Mexicana de Biodiversidad)
Research cruises aboard the R/V “El Puma” were organized to collect deep-water benthic and pelagic specimens off the Pacific coast of Mexico. Seventy four specimens of Holothuroidea were collected off the Pacific coast of Mexico in depths of 377-2 200 m. The collection includes representatives of 5 of the 6 orders of Holothuroidea, 3 Dendrochirotida, 2 Dactylochirotida, 2 Aspidochirotida, 4 Elasipodida and 2 Molpadiida. Apodida were not represented. Of the 13 species recognized, 11 were identified to species level and 2, belonging to the genera Ypsilocucumis Panning, 1949, and Mitsukuriella Heding and Panning, 1954, are new to science. Five species represent new geographic or depth records. A list of Mexican localities previously and newly reported for each species are plotted on distribution maps. Environmental data, i.e., depth, temperature, and dissolved oxygen measured at the bottom level during the survey are provided. When compared with other areas of the world, the reduced number of specimens collected during this survey could be linked to the limiting effect of the Pacific Mexico Oxygen Minimum Zone. An updated checklist of species of Holothuroidea recorded below 350 m depth along the Pacific coast of Mexico is also provided totaling 31 species: 13 of these occur in the California Current area, 20 in the Gulf of California, and 15 (16) along the SW coast of Mexico.